(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2025)
Aspects of Jewish history and culture in Oradea.This article presents an overview of the rich and complex history of the Jewish community in Oradea, a city in northwestern Romania. The presence of Jews in Oradea dates back to the 15th century, although their permanent settlement was initially forbidden. It was not until the early 18th century that they managed to settle in the city, especially in the outlying areas. The community experienced significant growth in the 19th century, peaking in the early 20th century when it accounted for about 5.4% of the city’s total population.